THE CONTRIBUTION OF HINDU BALINESE TRADITIONAL HEALING ON THE SUSTAINABLE DEVELOPMENT OF BALI - Nyoman Adiputra (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
The existence of tradition medicine in Bali is a factual thing. It is a part of Balinese culture, and it’s potency due to the three factors, such as: the written - unwritten sources of knowledge, providers, and the consumers. The traditional knowledge is written on the palm leaf (lontar). Lontar for traditional healings consist of tatwa or tutur (the philosophy, religion, cosmology, calendar, etc), lontar usadha (anatomy, physiology, patho-physiology, pharmacopea, and clinical textbooks). To be a traditional healer in Bali, there is no formal schooling. It is done very informally; and the process is ended based on two ways communication between the student/candidate and the teacher. The learning situation is performed in accordance with local culture, by a process of self acquired knowledge, individual learning, home works, and discussion. Practical aspect is based on observation on the self acquired knowledge processing. Everything is done through a process of initiation ceremony. By doing that, the Balinese’ traditional healer is guaranteed, a professional one. It will support the development’s process. The development is a must, and should be done until forever. Not just for this generation, but, for the further generation. Therefore, all resources should be taken into consideration, including the traditional medicine. The providers, and the natural resources in terms of medicinal plants, should be managed gently. Their roles and functions is a must for the sustainability. By doing that the efficient and effective development program could be achieved, implementing do the right thing and doing the thing right. That is the positive role of traditional medicine to the sustainable development. In doing that the development program should be based upon the both approaches (bottom up and top-down) for the equity effect to the all regions. That is in agreement with development program patron of Bali, based on agricultural sector, tourism, and small scale industry. By doing that it has been proven the prosperity of Balinese at a moment..